2011
DOI: 10.1080/87565641.2010.549985
|View full text |Cite
|
Sign up to set email alerts
|

Letters Rhyme: Electrophysiological Evidence From Children and Adults

Abstract: Event-related potentials (ERPs) and behavioral accuracy judgments were recorded in a letter name rhyming paradigm (e.g., A-J versus A-B) with 6- to 8-year-old beginning readers and adults. A typical N450 rhyming effect was evident for both children and adults, with few differences in mean amplitude or peak latency between groups. The size and timing of the electrophysiological effect were not correlated with standardized measures of phonological or reading ability, but accuracy in the ERP task was. Single lett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 52 publications
(60 reference statements)
9
30
0
Order By: Relevance
“…Mani and Plunkett (2011) suggested that target word recognition is reduced due to coactivation of other phonologically related words sounding similar to both the prime and the target. However, whereas onset priming in 2-year-olds results in interference effects (Mani & Plunkett, 2011), rhyme priming typically results in facilitation effects in 4-to 6-year-olds (Coch, Grossi, Skendzel, & Neville, 2005;Coch, Mitra, George, & Berger, 2011). Evidence from the current study also suggests facilitation in rhyme priming, although this was across languages.…”
Section: Discussionsupporting
confidence: 39%
“…Mani and Plunkett (2011) suggested that target word recognition is reduced due to coactivation of other phonologically related words sounding similar to both the prime and the target. However, whereas onset priming in 2-year-olds results in interference effects (Mani & Plunkett, 2011), rhyme priming typically results in facilitation effects in 4-to 6-year-olds (Coch, Grossi, Skendzel, & Neville, 2005;Coch, Mitra, George, & Berger, 2011). Evidence from the current study also suggests facilitation in rhyme priming, although this was across languages.…”
Section: Discussionsupporting
confidence: 39%
“…As has been reported in other ERP rhyming studies, participants in this experiment were quite accurate on the task overall, but less accurate in responding to rhymes than to nonrhymes (e.g., Coch, Hart, et al, 2008;Coch, Mitra, George, & Berger, 2011;Grossi et al, 2001). This pattern is consistent with the hypothesis of the rhyming effect as (at least in part) a phonological priming effect: Targets that phonologically match primes would theoretically require less processing, having been primed, than nonrhyming targets (e.g., Rouibah, Tiberghien, & Lupker, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…This pattern is consistent with the hypothesis of the rhyming effect as (at least in part) a phonological priming effect: Targets that phonologically match primes would theoretically require less processing, having been primed, than nonrhyming targets (e.g., Rouibah, Tiberghien, & Lupker, ). More resources spent on processing nonmatching targets may be related to greater accuracy for those targets (e.g., Coch et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Newman & Connolly, ), and in children as young as age 6 (e.g. Coch, Mitra, George & Berger, ; Grossi, Coch, Coffey‐Corina, Holcomb & Neville, ). It is also consistent with the view that the N400 reflects higher‐level integration across various levels of representations (e.g.…”
Section: Discussionmentioning
confidence: 99%